Relevansi Ajaran Tasawuf Bagi Kehidupan Muslim Di Era Modern - Rahmat Lutfi Guefara (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2023)
This research is motivated by the prevalence of materialistic culture among Muslim communities, where almost all aspects of life are assessed based on material values. In light of this, the author examines the relevance of Sufism teachings. This study employs a literature review method. The primary data sources are related to Sufism literature and the social conditions of Muslim communities. Secondary data sources include various writings from Sufismsm scholars and the works of Sufismsm practitioners in addressing various issues and providing solutions to the general public. The results show that Sufism ethics, as exemplified by Prophet Muhammad (PBUH), are highly relevant for application in the modern era. Additionally, various spiritual states such as qurbah (closeness to God), khauf (fear of God), and raja’ (hope in God) can contribute to inner peace and tranquility in daily life in the modern era. This is particularly effective in reducing the tendency of the soul to focus solely on materialism and outward needs.